Pregunta
upstudy study bank question image url

Let \( g(x)=5 x^{2}-3 \) (a) Find the average rate of change from -4 to 2 . (b) Find an equation of the secant line containing \( (-4, g(-4)) \) and \( (2, g(2)) \). (a) The average rate of change from -4 to 2 is \( \square \). (Simplify your answer.)

Ask by Valdez Ball. in the United States
Feb 21,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

(a) The average rate of change from -4 to 2 is 4.625. (b) The equation of the secant line is \( y = 4.625x - 0.75 \).

Solución

Solve the equation by following steps: - step0: Solve for \(g\): \(g\times 2=5\times 2^{2}-3\) - step1: Reorder the terms: \(2g=17\) - step2: Divide both sides: \(\frac{2g}{2}=\frac{17}{2}\) - step3: Divide the numbers: \(g=\frac{17}{2}\) Solve the equation \( g(-4) = 5(-4)^{2} - 3 \). Solve the equation by following steps: - step0: Solve for \(g\): \(g\left(-4\right)=5\left(-4\right)^{2}-3\) - step1: Reorder the terms: \(-4g=77\) - step2: Change the signs: \(4g=-77\) - step3: Divide both sides: \(\frac{4g}{4}=\frac{-77}{4}\) - step4: Divide the numbers: \(g=-\frac{77}{4}\) To solve the problem, we will follow the steps outlined: ### Part (a): Find the average rate of change from -4 to 2 The average rate of change of a function \( g(x) \) from \( x = a \) to \( x = b \) is given by the formula: \[ \text{Average Rate of Change} = \frac{g(b) - g(a)}{b - a} \] In this case, \( a = -4 \) and \( b = 2 \). We have already calculated: - \( g(-4) = -19.25 \) - \( g(2) = 8.5 \) Now, we can substitute these values into the formula: \[ \text{Average Rate of Change} = \frac{g(2) - g(-4)}{2 - (-4)} = \frac{8.5 - (-19.25)}{2 + 4} \] Calculating the numerator: \[ 8.5 + 19.25 = 27.75 \] Calculating the denominator: \[ 2 + 4 = 6 \] Now, substituting these into the average rate of change formula: \[ \text{Average Rate of Change} = \frac{27.75}{6} \] Now, let's simplify this fraction: \[ \text{Average Rate of Change} = 4.625 \] Thus, the average rate of change from -4 to 2 is: \[ \text{Average Rate of Change} = 4.625 \] ### Part (b): Find an equation of the secant line containing \( (-4, g(-4)) \) and \( (2, g(2)) \) The equation of a line can be expressed in point-slope form as: \[ y - y_1 = m(x - x_1) \] where \( m \) is the slope of the line, and \( (x_1, y_1) \) is one of the points on the line. The slope \( m \) can be calculated as: \[ m = \frac{g(2) - g(-4)}{2 - (-4)} = \frac{27.75}{6} = 4.625 \] Using the point \( (2, g(2)) = (2, 8.5) \): \[ y - 8.5 = 4.625(x - 2) \] Now, we can simplify this equation: \[ y - 8.5 = 4.625x - 9.25 \] Adding \( 8.5 \) to both sides: \[ y = 4.625x - 0.75 \] Thus, the equation of the secant line is: \[ y = 4.625x - 0.75 \] ### Summary of Results (a) The average rate of change from -4 to 2 is \( 4.625 \). (b) The equation of the secant line is \( y = 4.625x - 0.75 \).

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Mind Expander

To find the average rate of change of the function \( g(x) = 5x^2 - 3 \) from \( x = -4 \) to \( x = 2 \), we use the formula: \[ \text{Average rate of change} = \frac{g(2) - g(-4)}{2 - (-4)} \] First, calculate \( g(-4) \): \[ g(-4) = 5(-4)^2 - 3 = 5(16) - 3 = 80 - 3 = 77 \] Now, calculate \( g(2) \): \[ g(2) = 5(2)^2 - 3 = 5(4) - 3 = 20 - 3 = 17 \] Now plug these values into the average rate of change formula: \[ \text{Average rate of change} = \frac{17 - 77}{2 + 4} = \frac{-60}{6} = -10 \] So, the average rate of change from -4 to 2 is \( -10 \). Now, let's find the equation of the secant line using the points \( (-4, g(-4)) \) and \( (2, g(2)) \). The slope \( m \) of the secant line is the average rate of change we just calculated: \[ m = -10 \] Using the point-slope form of the line, \( y - y_1 = m(x - x_1) \), we can use the point \( (2, 17) \): \[ y - 17 = -10(x - 2) \] Simplifying this, we get: \[ y - 17 = -10x + 20 \quad \Rightarrow \quad y = -10x + 37 \] Thus, the equation of the secant line is \( y = -10x + 37 \). In summary: (a) The average rate of change from -4 to 2 is \( -10 \). (b) The equation of the secant line is \( y = -10x + 37 \).

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad